Aplicação do extrato de coentro (Coriandrum sativum L.) na elaboração de linguiça suína cozida - Meireles, Theresa Paula Felix da Silva (2019)
Scientific evidence indicates that the high consumption of processed meat products is related to the incidence of malignant neoplasms, especially colorectal cancer. In this context, consumer interest has been increasing for reformulated products with a minimum residual nitrite content and added natural ingredients. Vegetables not only provide nitrite indirectly but also provide bioactive and antioxidant compounds that can enrich the end product and minimize the formation of potentially carcinogenic substances. Thus, the objective of this work was to evaluate the effect of coriander (Coriandrum sativum L.) extract application on cooked pork sausages during refrigerated storage (4 ºC). Four treatments were performed: F1 (Control Formulation) = no curing salt and no coriander extract added; F2 (Standard Formulation) = added curing salt; F3 = with 0.29% coriander extract added; F4 = with addition of 0.58% coriander extract. The extract was evaluated for pH, color, antioxidant activity and antimicrobial activity against E. coli and S. aureus. The sausages were characterized for centesimal composition (moisture, ashes, protein, lipids and carbohydrates). During 30 days of cold storage (4 ° C) the sausages were evaluated for residual nitrate and nitrite levels, pH, Aw, TBARS and color. The use of coriander extract did not influence the protein, lipid and carbohydrate contents of the formulations. However, there was a significant difference for moisture and ash values. In formulations added with coriander extract the residual nitrate levels were within normative standards while residual nitrite levels were below the lower limit detectable by the method used (<5mg.kg-1). Regarding to TBARS values, F2 presented the lowest values. However, the use of coriander extract was also effective in controlling lipid oxidation during storage. Coriander extract application resulted in lower pH values and also in less tendency to develop red color (a*). Thus, the application of coriander extract may be used to reduce the amount of nitrite added in these products, as it has been shown to have an effect on lipid oxidation control.